EP 33. Prolonged pauses in verbal fluency tasks under active VIM-DBS – Does it delay automatic lexical co-activation?. Issue 9 (September 2016) - Ehlen, F.; Vonberg, I.; Fromm, O.; Kühn, A.A.; Klostermann, F.
Abstract : Background: Deep Brain Stimulation (DBS) of the thalamic ventral intermediate nucleus (VIM) is a common therapeutic option for patients with essential tremor (ET). Despite a generally low risk of side effects, declines in verbal fluency performance have previously been reported. Objectives: This study aimed at specifying effects of VIM-DBS on the two main subcomponents of verbal fluency output, i.e., lexical clustering and switching. This approach was chosen in order to discriminate between DBS effects on automatic activation within lexical fields (during clusters) and on attention demanding processes (switches). Patients & methods: Thirteen ET patients with VIM-DBS performed verbal fluency tasks in their VIM-DBS ON and OFF conditions. Analysis of clusters and switches were accomplished on the basis of curve fittings using an improved mathematical function for the description of word output dynamics. All results were compared to those of fifteen healthy control subjects, and significant OFF-ON-change scores were correlated to stimulation parameters. Results: In addition to a reduction in the number of words produced, the intervals between words within clusters were significantly prolonged in the DBS ON vs. OFF condition. This effect correlated with a more anterior electrode position. Switches were not affected by DBS but took longer in patients than in controls. Conclusion: VIM-DBS seems to impair verbal fluency primarily on the level of automatic lexical co-activation. This finding is discussed in the context of the hypothesized role of the thalamus in lexical processing. More posterior electrode positions appear safer in this regard.